LncRNA HAGLR silencing inhibits IL-1β-induced chondrocytes inflammatory injury via miR-130a-3p/JAK1 axis - Yunzhou Zuo; Changjun Xiong; Xuewen Gan; Wei Xie; Xiaokang Yan; Yanzhao Chen; Xugui Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoarthritis (OA), the most common form of arthritis, is accompanied by destruction of articular cartilage, development of osteophyte and sclerosis of subchondral bone. This study aims to explore whether lncRNA HAGLR can play a role in OA, and further clarify the potential mechanism. Material and methods StarBase and luciferase reporter assay were applied for predicting and confirming the interaction between lncRNA HAGLR, miR-130a-3p and JAK1. The levels of lncRNA HAGLR and miR-130a-3p were analyzed using quantitative reverse transcription PCR (qRT-PCR). The proliferation, cytotoxicity and apoptosis of CHON-001 cells were evaluated by MTT, lactate dehydrogenase assay (LDH) and Flow cytometry (FCM) analysis, respectively. Moreover, expression of cleaved Caspase3 protein were determined by Western blot assay. The release of inflammatory factors (TNF-α, IL-8, and IL-6) was detected by ELISA. Results lncRNA HAGLR directly targets miR-130a-3p. Level of lncRNA HAGLR was substantially higher and miR-130a-3p level was memorably lower in IL-1β stimulated CHON-001 cells than that in Control group. Furthermore, lncRNA HAGLR silencing alleviated IL-1β induce chondrocyte inflammatory injury, as evidenced by increased cell viability, reduced LDH release, decreased apoptotic cells, inhibited cleaved-Caspase3 expression, and reduced secretion of secretion of inflammatory factors. However, miR-130a-3p-inhibitor reversed these findings. We also found miR-130a-3p directly targeted JAK1 and negatively regulated JAK1 expression in CHON-001 cells. In addition, JAK1-plasmid reversed the effects of miR-130a-3p mimic on IL-1β-induced chondrocytes inflammatory injury. Conclusion Silencing of lncRNA HAGLR alleviated IL-1β-stimulated CHON-001 cells injury through miR-130a-3p/JAK1 axis, revealing lncRNA HAGLR may be a valuable therapeutic target for OA therapy.